Para além de partidas e de chegadas: migração e imaginário entre o Brasil e a França, na contemporaneidade - Marina Alves Amorim (2009)
The object of this historical research is the contemporary images of the French about Brazil and of Brazilians about France. Considering the imaginary not as the opposite from what is real but as one of its aspects, this research proposes to unveil the imaginary which currently interconects Brazil and France, without losing sight of its historical perspective. For this purpose, the selected starting point is the Brazilian and French imaginary itself, surfaced in oral history interviews. Fifteen French citizens who live or have lived in Brazil were interviewed, along with six others who were traveling or have once traveled to Brazil and six who have never been here; eighteen Brazilian citizens who live or have lived in France were also interviewed, along with four Brazilians who were traveling or have traveled to France and six ones who have never been in France. Ending the row, five French Brazilians were interviewed. When analysing the reserach sources, migrant testimonies were given priority, considering as this either the French who live or have lived in Brazil or the Brazilians who live or have lived in France. And, among the temporary migrants, special attention was granted to those who have moved to study. The answer to five questions was pursued along this thesis. What would take Brazilians to permanently move to Rennes (France)? What would make the French settle in Belo Horizonte? Why would Brazilians go study in France? Why would the French come to study in Brazil? What would the migration motives say about the chosen places imaginary as a migration destination? It is therefore by means of this journey, represented by the migration, that we have tried to catch the imaginary about the other as seen by the migrant.